2018
DOI: 10.1089/lap.2018.0092
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cholecystectomy for Acute Cholecystitis in Elderly Patients Treated Primarily with Antibiotics or Percutaneous Drainage of the Gallbladder

Abstract: In elderly patients with acute cholecystitis, DC can be a good alternative to EC. However, after percutaneous drainage DC is associated with high complication rate and long hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Delayed management may lead the aggravation to severe cholecystitis situations that increases morbidity such as gangrenous changes, perforation, etc. [3]. The Tokyo Guidelines (TG 18), which include criteria that are classified as clinical markers and ultrasonography (USG) findings of inflammation, are often used for diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed management may lead the aggravation to severe cholecystitis situations that increases morbidity such as gangrenous changes, perforation, etc. [3]. The Tokyo Guidelines (TG 18), which include criteria that are classified as clinical markers and ultrasonography (USG) findings of inflammation, are often used for diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether early cholecystectomy is superior to non-surgical treatment for elderly patients with AC was not determined in this study. However, the mortality and morbidity rate after early cholecystectomy were 0.0 and 11.9%, respectively, which were acceptable considering previous studies on other treatment strategies for AC in elderly patients [16, 17]. Further prospective studies are needed to reveal the preoperative cognitive status and the efficacy of the surgical treatment for elderly patients with AC.…”
Section: Discussionmentioning
confidence: 83%
“…The association between complications and the interval from PTGBD to cholecystectomy has previously been discussed in small studies. 4,6,[8][9][10]18,19 An earlier report showed that intervals of <72 h was associated with a higher incidence of postoperative complications, compared with intervals of 72 h. 5 Another existing report showed comparable results for postoperative complications for patients with intervals of <10 days and those with intervals of 10 days. 19 Other previous reports comparing early cholecystectomy without PTGBD and delayed cholecystectomy, performed with intervals of >4-6 weeks following PTGBD, showed a lower incidence of complications in the delayed cholecystectomy group.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 PTGBD is selected to avoid urgent surgery in highrisk patients and is an effective procedure to relieve symptoms from acute cholecystitis. 4 Subsequent cholecystectomy is required if the patient can tolerate surgery because of high a recurrence rate of acute cholecystitis. Acute inflammation, adhesion, and fibrous change are the main concerns when surgeons determine the timing of cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%